Taking from the rural to serve the urban: the Likhubula water project and the slow violence of water abstraction in Malawi - Namusanya, Dave (Criminological encounters, 2022)
Despite community protests in the Mulanje District of Southern Malawi, the Malawi government in November 2016 launched a $23.5 million project to abstract water from the Likhubula River in rural Mulanje and transport it almost 70 kilometres away to Malawi’s commercial capital of Blantyre. Drawing on findings from ongoing ethnographic observations in Southern Malawi, this paper presents the Likhubula Water Project as a form of slow violence causing socialharms that perpetuate colonial legacies. It engages with the complexities of the project, recognisingthe pressure placed on water resources as a socio-political need in response to the impacts of climate change, population growth and rapid urbanisation while at the same time identifying this as a form of slow violence in which the harms from the water project are not only in the ‘mining’ of water to benefit urban life but also in terms of the disregard for the significance of the water to local communities. We conclude that the act of exposing the area to water exploration and exploitation presents the possibility of perpetuating other forms of environmental harm in areas where there is already significant pressure on land, forest and water resources.